Too cynical to reconnect: Cynicism moderates the effect of social exclusion on prosociality through empathy - CHOY, Bryan K. C. (Institutional Knowledge at Singapore Management University, 2021)
Extant findings are mixed on whether social exclusion impacts prosociality. We propose one factor that may underlie the mixed results: Cynicism. Specifically, cynicism may moderate the exclusion-prosociality link by influencing interpersonal empathy. Compared to less cynical individuals, we expected highly cynical individuals who were excluded to experience less empathy and, consequently, less prosocial behavior. Using an online ball-tossing game, participants were randomly assigned to an exclusion or inclusion condition. Consistent with our predictions, the effect of social exclusion on prosociality through empathy was contingent on cynicism, such that only less-cynical individuals responded to exclusion with greater empathy, which, in turn, was associated with higher levels of prosocial behavior. We further showed this effect to hold for cynicism, but not other similar traits typically characterized by high disagreeableness. Findings contribute to the social exclusion literature by suggesting a key variable that may moderate social exclusion's impact on resultant empathy and prosocial behavior and are consistent with the perspective that people who are excluded try to not only become included again but to establish alliances characterized by reciprocity.